Performance Study of Non-Contact Membrane Distillation Engineering Prototype for Treatment of Radioactive Wastewater - Bao-lin WANG; De-tao XIAO; Zheng-zhong HE; Xing-feng YANG; Cheng-lin LI (He huaxue yu fangshe huaxue)
The non-contact membrane distillation(MD) method developed by researchers at the University of South China marks a notable advancement over traditional direct contact membrane distillation approaches. Conventional MD methods encounter substantial limitations, such as shortened membrane lifespan due to continual contact with contaminants, low and inconsistent membrane flux, and inadequate mechanisms for real-time membrane damage monitoring. These challenges significantly reduce the operational efficiency and reliability of MD in practical applications, particularly in environments where stable, uninterrupted performance is critical. The non-contact MD method, however, minimizes the direct interaction between the membrane and feed solution, thereby markedly extending the membrane’s functional lifespan and enhancing its flux stability, rendering it more suitable for long-term, large-scale deployment. This study aims to adapt the non-contact MD technique for on-site volume reduction and purification of radioactive wastewater generated by nuclear power plants, hospitals, and similar facilities. To meet the specific requirements of these applications, the researchers referenced established design frameworks for non-contact MD devices and incorporated heat pump waste heat recovery technology. This integration not only improves energy efficiency but also addresses the need for an economical and practical treatment system. By utilizing heat pump technology, energy consumption in the MD process is reduced by approximately 26%, with projected energy use maintained below 500 kW•h per ton of wastewater treated. Such energy efficiency is essential for large-scale application, enhancing both the economic feasibility and sustainability of radioactive wastewater treatment. A pilot-scale engineering prototype was designed, constructed, and rigorously evaluated to determine its performance metrics. Experimental results indicate that the prototype achieves a robust membrane flux of over 20 kg/(m2•h). Additionally, the prototype’s wastewater treatment capacity is flexible, ranging from 16.58 kg/h to 75.15 kg/h based on operational settings. This adjustable treatment capacity allows operators to calibrate the processing rate in real time, aligning the system’s functionality with varying demands and expanding its applicability across diverse use cases. The prototype demonstrated superior ion removal efficiency for wastewater treatment. Conductivity assessments revealed an ion removal efficiency of 99.7%, while retention rates for simulated radioactive contaminants such as strontium(Sr2+) and iodine(I−) surpassed 99.9%. These findings underscore the prototype’s capability to treat radioactive wastewater effectively, ensuring that the treated effluent meets stringent environmental safety standards. In summary, the successful design and validation of this engineering prototype establish a robust technical foundation for the future development of compact, on-site radioactive wastewater treatment systems. Such systems have the potential to substantially mitigate the environmental impact of radioactive wastewater from nuclear and healthcare facilities, advancing safer, more sustainable waste management solutions.